Faktor Yang Berhubungan Dengan Kejadian Berat Badan Balita Dibawah Garis Merah (BGM) Di Wilayah Kerja Puskesmas Martapura Barat Kabupaten Banjar Tahun 2019 - Luthfia, Luthfia; Maslani, Noorhayati; rusmilawaty, rusmilawaty; Tunggal, Tri (JURNAL KEBIDANAN BESTARI, 2023)
This research uses a cross sectional approach. The independent variables are family income, meal frequency, basic immunization status and the dependent variable is the incidence of under-five children (BGM). Samples were taken using a type-type sampling technique of 237 toddlers. The research instruments used KMS for toddlers, questionnaires, registers for toddlers, and scales. Data processing using the Chi square statistical test with α = 0.05 with a confidence level of 95%. The results of the study showed that there was a relationship between family income and the incidence of BGM under five (ρ=0.000), a relationship between eating frequency and the incidence of BGM under five (ρ=0.003), and a relationship between basic immunization status and the incidence of BGM under five (ρ=0.004). The results of this research show a relationship between family income, frequency of eating, basic immunization status and the incidence of BGM in the West Martapura Health Center work area in 2019.